President’s Message - McLeod, Bonnie (Operating Room Nurses Association of Canada Journal, 2010)
As we progress quickly through 2010 I am reminded of the saying “the past is a prologue to the future.” Knowing where we’ve come from, and where we’re going, is essential if we are going to actually get anywhere.